Changing perceptions and transforming outcomes : L&T's acquisition of Mindtree - Kaul, Asha; Agarwalla, Sobhesh Kumar (London : Indian Institute of Management, Ahmedabad, 2020)
On March 18, 2019, after intense brainstorming for over an hour, Yuvraj Mehta, head, of Corporate Brand Management and Communications (CBMC) at Larsen & Toubro (L&T), came out of a meeting with S. N. Subrahmanyan, CEO, and MD, and headed towards his room. The crease on his brow and slow gait indicated that all was not well.The reason: a negative media narrative of L&T following the announcement of the intended high-profile merger and acquisition (M&A) of Mindtree Limited (hereafter Mindtree). Both traditional and social media were rife with speculations, reports, and allegations against L&T, such as "Hostile takeover" and "Destruction of Mindtree's culture." Faced with intense negative publicity, Mehta wondered how he could positively influence all stakeholders - media, employees, investors, bankers, shareholders, and the government; turn the tide and change the narrative from a hostile takeover to that of continuity, growth, and profitability; and, finally, integrate Mindtree, its employees and culture with L&T.Media speculations began in January 2019 when L&T, the engineering and construction giant, planned to acquire a majority stake in the young IT firm, Mindtree. In less than a month, media reporting changed to aggressive ranting. Mehta, who had joined L&T in February 2019, was tasked with the responsibility of handling the media and managing crisis communication. Mehta knew he had to act fast. Time was at a premium. He quickened his pace, reached his room, and picked up the phone. Given the social media affordances, he knew that along with his team he had to begin strategizing immediately. He tapped his pencil restlessly as he waited for his colleagues to join him.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Stakeholder management -- Case studies; Consolidation and merger of corporations -- Case studies; Business planning -- Case studies